Physical Activity, Functional Status, and Quality of Life Among Older Adults in India - Porkodi Arjunan; Manjula Annamalai; Aruna Subramaniam; Judie Arulappan (SAGE Publishing, 2024)
Introduction Physical activity and social engagement protect older adults against functional decline and improve their quality of life. Physical inactivity poses an increased risk for noncommunicable diseases. Globally, one in four adults is physically inactive. Enhancing the physical activity of older adults is crucial not only for increasing their life expectancy but also for improving their functional status and quality of life. Objective This study aimed to evaluate the physical activity, functional status, and quality of life of older adults attending the medical outpatient department of a tertiary care hospital in Chennai, Tamil Nadu, India. Methods The study adopted a descriptive cross-sectional research design. A total of 100 female and male patients above 65 years of age with comorbid conditions attending the medical outpatient department participated in the study. The sociodemographic and clinical characteristics of these patients were assessed. In addition, the Rapid Assessment of Physical Activity, Katz Index of Independence in Activities of Daily Living, Lawton Instrumental Activities of Daily Living Scale, and Older People Quality of Life Questionnaire were used to measure the physical activity, functional status, and quality of life of patients. The data were analyzed using descriptive and inferential statistics. Results Among the participants, only 17% were active, and 35% were underactive for regular light activities. Approximately 81% did not perform any activity to improve their muscle strength or flexibility. In 56% of the participants, disability was present. The majority mentioned that they experienced difficulties in preparing food and shopping. Regarding the quality of life of the participants, the mean ± standard deviation score was 77.38 ± 9.03. Significant results were found in the domains of independence, control over life, and freedom. The overall quality of life was not related to leisure and activities, financial circumstances, the Instrumental Activities of Daily Living Scale score, the Rapid Assessment of Physical Activity 2 score, and the Rapid Assessment of Physical Activity 1 score. The quality of life was weakly related to emotional and psychological well-being, control over life, home and neighborhood, freedom, independence, and social relationships. Conclusion Limited physical activity and poor functional status impact the quality of life of older adults. Therefore, educational and physical interventions should be implemented at the hospital and community levels to improve the physical activity, functional status, and quality of life of older adults.